2017
DOI: 10.1016/j.jmoldx.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Targeted RNA Sequencing Assay for Kinase Fusion Detection in Solid Tumors

Abstract: Kinase gene fusions are important drivers of oncogenic transformation and can be inhibited with targeted therapies. Clinical grade diagnostics using RNA sequencing to detect gene rearrangements in solid tumors are limited, and the few that are available require prior knowledge of fusion break points. To address this, we have analytically validated a targeted RNA sequencing assay (OSU-SpARKFuse) for fusion detection that interrogates complete transcripts from 93 kinase and transcription factor genes. From a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 59 publications
0
60
0
Order By: Relevance
“…Multiple RNA NGS sequencing quality control strategies and metrics have been described in the literature. These include spike-in control transcripts and corresponding probes to assess efficiency of hybrid capture and indirectly assess RNA quality 11 ; probes to RNA from housekeeping genes to assess RNA quality 11 ; a minimum total mapped read count 10,11,13 ; a minimum on-target rate 11 ; a minimum mapped exon-exon junction read count 10 ; a percent of mapped reads that map to coding regions 10 ; and qPCR-based assessment of RNA quality 13 . The utility of these metrics needs to be weighed against the theoretical possibility of detecting a highly expressed fusion despite poor quality, or of missing a lowly expressed fusion despite high quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple RNA NGS sequencing quality control strategies and metrics have been described in the literature. These include spike-in control transcripts and corresponding probes to assess efficiency of hybrid capture and indirectly assess RNA quality 11 ; probes to RNA from housekeeping genes to assess RNA quality 11 ; a minimum total mapped read count 10,11,13 ; a minimum on-target rate 11 ; a minimum mapped exon-exon junction read count 10 ; a percent of mapped reads that map to coding regions 10 ; and qPCR-based assessment of RNA quality 13 . The utility of these metrics needs to be weighed against the theoretical possibility of detecting a highly expressed fusion despite poor quality, or of missing a lowly expressed fusion despite high quality.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent years, NGS-based fusion detection techniques have been developed. These include genomic DNA sequencing with target enrichment for regions in which breakpoints occur (such as selected “hotspot” introns) 8,9 , whole-transcriptome RNA sequencing utilizing poly(A) capture 10 , and targeted RNA sequencing employing hybridization-based capture 11,12 or anchored multiplex PCR 13 . Broadly speaking, NGS-based techniques offer the advantage of greater breadth, depth, and resolution compared to traditional methods, with a tradeoff of increased cost.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the most popular commercially available DNA NGS panels, such as Foundation One, may not detect certain NTRK fusions. The addition of RNAseq to NGS testing has shown high sensitivity and specificity rates, 93% and 100% respectively, in detecting clinically actionable gene fusions (39). Data showed that RNAseq had led to unbiased results as well.…”
Section: Detection Of Ntrk Fusionsmentioning
confidence: 99%
“…However, not all assays detect certain NTRK fusions, especially NTRK2 and NTRK3 rearrangements. The addition of targeted RNA sequencing, as a complementary method to NGS, has been associated with a sensitivity rate of 93% and a specificity rate of 100% [11]. FISH and RT-PCR could be an alternative to DNA-NGS, especially for cancer subtypes with high prevalence of NTRK rearrangements.…”
Section: Detection Of Ntrk Fusionsmentioning
confidence: 99%